Temperature-resistant and salt-resistant stable foam agent for carbon dioxide flooding and preparation method thereof

CN122381789BActive Publication Date: 2026-10-16DESHI ENERGY TECH GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610839774.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-11
Publication Date
2026-10-16
Estimated Expiration
2046-06-11

AI Technical Summary

Technical Problem

[0006]为了解决上述问题,提供了一种耐温耐盐型二氧化碳驱油用稳泡剂及其制备方法,通过对稳泡剂的组分组成进行限定,可有效解决现有稳泡剂耐盐抗聚沉、耐高温抗降解不足等问题,各组分协同性强,且制备工艺简单、可工业化,药剂配伍性好、油藏低伤害,可显著提升CO2泡沫稳定性与原油采收率,实用性强

Benefits of technology

1.根据本申请的耐温耐盐型二氧化碳驱油用稳泡剂,本申请通过磺酸甜菜碱-氟碳共聚物与脂肪醇聚氧乙烯醚磺酸盐协同,既实现强耐盐抗CO2萃取,又抑制氟碳组分引发的乳化隐患;聚多巴胺包覆改性纳米ZnO与季铵化羟丙基淀粉协同作用,既发挥纳米颗粒的耐高温抗降解、强化泡沫液膜作用,又解决其吸附伤害与孔喉堵塞问题;氨基三亚甲基膦酸与羧甲基改性黄原胶辅助增效,全面解决现有稳泡剂耐盐不足、高温失效、纳米吸附等痛点,适配高温高盐油藏苛刻环境。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a temperature-resistant and salt-resistant foam stabilizer for carbon dioxide oil displacement and a preparation method thereof, and belongs to the technical field of chemical agents for carbon dioxide oil displacement. The temperature-resistant and salt-resistant foam stabilizer for carbon dioxide oil displacement comprises, in mass fraction, 0.8-1.2% of sulfobetaine-fluorocarbon copolymer, 0.12-0.2% of fatty alcohol polyoxyethylene ether sulfonate, 0.2-0.3% of modified nano ZnO, 0.08-0.12% of quaternized hydroxypropyl starch, 0.05-0.10% of aminotri (methylene) phosphonic acid, 0.05-0.08% of carboxymethyl modified xanthan gum and the balance of water, wherein the modified nano ZnO is prepared by coating nano ZnO with polydopamine. By limiting the component composition of the foam stabilizer, the problems of the existing foam stabilizer, such as insufficient salt resistance, poor anti-agglomeration, insufficient high-temperature resistance and poor degradation resistance, can be effectively solved. The components have strong synergism, the preparation process is simple and industrialized, the agent has good compatibility, the reservoir has low damage, the foam stability of CO2 and the oil recovery rate can be remarkably improved, and the foam stabilizer has high practicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a temperature- and salt-resistant foam stabilizer for carbon dioxide flooding and its preparation method, belonging to the technical field of carbon dioxide flooding chemical agents. Background Technology

[0002] As oil and gas exploration and development extend to deeper and ultra-deep reservoirs, the development of high-temperature and high-salinity reservoirs has become a key area for enhancing oil recovery. CO2 foam flooding technology, with its excellent mobility control, gas channeling suppression, and swept volume expansion, has become one of the core technologies for improving oil recovery in high-water-cut, low-permeability, tight, high-temperature, and high-salinity reservoirs. Its core principle is to construct a stable CO2 foam system using foam stabilizers, relying on the Jamin effect of the foam to block high-permeability channels, inhibit CO2 gas channeling, and promote full contact between CO2 and crude oil, achieving efficient displacement.

[0003] However, deep, high-temperature, and high-salinity oil reservoirs generally have high formation temperatures, high formation water salinity, and are rich in Ca². + Mg² + In harsh environments with high-valence metal ions, existing CO2 foam flooding stabilizers are ill-suited to these reservoir conditions, exhibiting numerous technical shortcomings that severely restrict the large-scale application of CO2 foam flooding technology. Firstly, existing foam stabilizers lack sufficient salt resistance, making them vulnerable to interference from high salinity and high-valence metal ions. Conventional foam stabilizers often employ single sulfonate or betaine surfactants, which are susceptible to damage from Ca²⁺ in high-salt environments. + Mg² + Electrostatic shielding and complexation can lead to salting out, aggregation, or stratification, resulting in loss of interfacial activity and the inability to form a stable gas-liquid interfacial film, causing rapid foam collapse. Secondly, poor high-temperature stability is another core defect of existing foam stabilizers. Under high-temperature conditions, the molecular chains of conventional foam stabilizers are prone to hydrolysis, thermo-oxidative chain scission, and oxidative degradation, leading to the failure of the agent structure, a significant shortening of the foam half-life, and the inability to achieve long-term foam stabilization.

[0004] Existing technologies include solutions that improve resistance to high-temperature degradation by introducing nanoparticles, such as introducing nano-ZnO and other metal oxide nanoparticles as foam stabilizers to enhance the strength of the foam liquid film using their rigid structure. However, nano-ZnO has high surface activity and is prone to strong adsorption and pore throat retention on rock surfaces, which not only causes a large loss of reagents but also leads to pore throat blockage and reservoir damage.

[0005] Therefore, there is an urgent need to develop a temperature- and salt-resistant foam stabilizer for CO2 flooding that can simultaneously solve the problems of high-salt precipitation and high-temperature degradation while reducing derivative problems such as nanoparticle adsorption damage, so as to adapt to the harsh conditions of high-temperature and high-salt reservoirs and promote the efficient and large-scale application of CO2 foam flooding technology. Summary of the Invention

[0006] To address the aforementioned issues, a temperature- and salt-resistant foam stabilizer for carbon dioxide flooding and its preparation method are provided. By limiting the composition of the foam stabilizer, the problems of insufficient salt resistance, anti-agglomeration, high-temperature resistance, and anti-degradation of existing foam stabilizers can be effectively solved. The components have strong synergistic effects, and the preparation process is simple, industrializable, and has good compatibility with the reagents, resulting in low reservoir damage. It can significantly improve the stability of CO2 foam and the recovery rate of crude oil, making it highly practical.

[0007] According to one aspect of this application, a temperature- and salt-resistant foam stabilizer for carbon dioxide flooding is provided, comprising, by mass fraction, 0.8% to 1.2% sulfonate betaine-fluorocarbon copolymer, 0.12% to 0.2% fatty alcohol polyoxyethylene ether sulfonate, 0.2% to 0.3% modified nano-ZnO, 0.08% to 0.12% quaternized hydroxypropyl starch, 0.05% to 0.10% aminotrimethylene phosphonic acid, 0.05% to 0.08% carboxymethyl modified xanthan gum, with the balance being water; wherein the modified nano-ZnO is prepared by polydopamine-coated nano-ZnO.

[0008] Specifically, the sulfonate betaine-fluorocarbon copolymer provides basic salt resistance and CO2 extraction resistance. The sulfonate groups in its molecule can work together with the sulfonate groups of fatty alcohol polyoxyethylene ether sulfonate to synergistically resist salt. Fatty alcohol polyoxyethylene ether sulfonate improves its solubility and inhibits emulsification. Aminotrimethylene phosphonic acid further chelates high-valence metal ions, enhancing the salt resistance effect. Modified nano-ZnO is resistant to high temperature and degradation, and quaternized hydroxypropyl starch inhibits its adsorption damage. Carboxymethyl modified xanthan gum assists in foam stabilization and viscosity enhancement. The components complement and synergistically address the pain points of existing foam stabilizers such as insufficient temperature and salt resistance, nano-adsorption, and system emulsification. It is suitable for high-temperature and high-salt oil reservoirs, achieving long-term foam stabilization with low damage to the oil reservoir and strong practicality.

[0009] Optionally, the sulfonate betaine-fluorocarbon copolymer is prepared by the following steps: S1. Methacryloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate and hydroxyethyl methacrylate are placed in a three-necked flask, DMSO solvent is added, the temperature is raised to 70~75℃ and stirred. S2 was added dropwise with an initiator solution under a nitrogen atmosphere and stirred at 70-75°C for 6-8 hours. S3 was cooled to 50-55℃, and isocyanate propyltriethoxysilane solution was added dropwise. The mixture was stirred for 2-3 hours, cooled to room temperature, precipitated with anhydrous ethanol, centrifuged, washed, and dried to obtain sulfonate betaine-fluorocarbon copolymer.

[0010] Specifically, the three monomers are copolymerized in DMSO solvent to obtain a copolymer with side chains containing sulfobetaine, fluorocarbon hydrophobic segments, and hydroxyl groups. Then, urethane CO2-responsive groups are grafted onto isocyanate propyltriethoxysilane. The sulfonate groups inherent in the copolymer interact with the sulfonate groups of the fatty alcohol polyoxyethylene ether sulfonate to achieve strong chelation, strong salt resistance, and shielding against Ca²⁺. + Mg² + It inhibits salt precipitation and precipitation; fluorocarbon segments enhance interfacial adsorption strength, resist supercritical CO2 extraction and dissolution, and stabilize the gas-liquid interface film; CO2-responsive groups can undergo reversible protonation with formation CO2 concentration, adaptively adjusting molecular hydrophilicity and hydrophobicity to achieve formation foam stabilization and enhancement; the scientific and controllable steps ensure the stability of the copolymer structure, retaining the salt resistance of sulfonate groups and the interfacial strengthening effect of fluorocarbon chains, while also endowing it with CO2 responsiveness, synergistically achieving formation foam stabilization and production-end foam breaking linkage with other components, and the preparation process is simple and industrializable.

[0011] Optionally, the molar ratio of methacryloyloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate and hydroxyethyl methacrylate is (7~8):(2~3):(0.5~0.6).

[0012] Specifically, this application balances the hydrophilicity and hydrophobicity of the copolymer by limiting the molar ratio of the three monomers. Methacryloxyethyl-N,N-dimethylpropanesulfonate provides strong salt-resistant groups, while perfluorohexylethyl acrylate enhances resistance to CO2 extraction. Excessive or insufficient proportions will result in either insufficient salt resistance or severe emulsification of the copolymer. This formulation gives the copolymer both excellent salt resistance and compatibility, allowing it to synergistically eliminate emulsification risks with fatty alcohol polyoxyethylene ether sulfonate, while providing a suitable molecular structure for grafting CO2-responsive groups. This ensures synergistic effects between the copolymer and other components in the system, improving the overall salt resistance and foam stabilization performance of the foam stabilizer.

[0013] Optionally, the initiator solution is azobisisobutyronitrile with a mass concentration of 5% to 6%; the amount of the initiator is 2% to 3% of the total mass of methacryloyloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate and hydroxyethyl methacrylate.

[0014] Specifically, this application limits the parameters related to the initiator. On the one hand, it avoids the residue of unreacted monomers. On the other hand, it prevents the excessive amount of initiator from causing uneven molecular weight of the copolymer, so that the molecular weight distribution of the copolymer is reasonable and the structure is stable, ensuring its salt resistance and CO2 extraction resistance. When it works in synergy with components such as modified nano ZnO and quaternized hydroxypropyl starch, it can enhance the interfacial film strength, avoid the overall synergistic effect of the foam stabilizer due to the performance defects of the copolymer, and improve the stability of the system.

[0015] Optionally, the mass concentration of the isocyanate propyltriethoxysilane solution is 8% to 10%; the solvent of the isocyanate propyltriethoxysilane solution is anhydrous ethanol; and the amount of DMSO solvent used is 3 to 4 times the total mass of methacryloyloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate, and hydroxyethyl methacrylate.

[0016] Specifically, this parameter ensures high grafting efficiency and uniform structure of the copolymer, stable CO2 response performance, and synergistic enhancement of salt resistance with aminotrimethylenephosphonic acid in the system. At the same time, it avoids the influence of modifier residue on component compatibility, ensures that all components of the foam stabilizer work synergistically, and improves temperature and salt resistance and response performance.

[0017] Optionally, the preparation method of the modified nano zinc oxide includes the following steps: S01. Nano ZnO was dispersed in Tris-HCl buffer solution and ultrasonically dispersed for 30-60 min to obtain a uniformly dispersed nano ZnO suspension. Dopamine hydrochloride was added to the SO2 nano-ZnO suspension and stirred at room temperature and in air atmosphere for 12-16 hours to allow dopamine to be deposited in situ on the surface of nano-ZnO to form a polydopamine coating layer. After the SO3 reaction is complete, the precipitate is collected by centrifugation, washed with deionized water, and dried at 50-60℃ to obtain modified nano-ZnO.

[0018] Specifically, ultrasonic dispersion in Tris-HCl buffer ensures uniform dispersion of nano-ZnO, while in-situ self-polymerization of dopamine hydrochloride forms a coating layer that inhibits nano-ZnO aggregation and adsorption. The modified nano-ZnO prepared by this process has an outer polydopamine layer that can capture high-temperature free radicals, inhibiting the thermo-oxidative degradation and hydrolytic chain scission of organic components, and providing long-term high-temperature resistance. The inorganic nano-core and quaternized hydroxypropyl starch synergistically inhibit adsorption damage. It also weakly catalyzes the CO2 hydration reaction to generate bicarbonate, which can further enhance the synergistic effect of the CO2 response of the system. At the same time, it synergistically enhances the foam stabilizing effect with sulfonated betaine-fluorocarbon copolymer, solving the problems of poor dispersion and easy adsorption of unmodified nano-ZnO, and ensuring the high-temperature resistance and low-damage characteristics of the foam stabilizer.

[0019] Optionally, the mass-to-volume ratio of the nano-ZnO to the Tris-HCl buffer is 5-8 g / L; the amount of dopamine hydrochloride used is 40%-60% of the mass of the nano-ZnO.

[0020] Specifically, a formulation ratio of 5-8 g / L ensures uniform dispersion of nano-ZnO, while 40%-60% dopamine hydrochloride forms a complete coating layer. This avoids both insufficient coating leading to nano-ZnO agglomeration and excessive coating affecting its catalytic synergistic effect. As a result, the modified nano-ZnO exhibits good dispersibility and strong anti-adsorption capacity. It synergistically inhibits reservoir damage with quaternized hydroxypropyl starch and enhances foam stability with carboxymethyl modified xanthan gum. At the same time, it assists in the CO2 response effect of sulfonate betaine-fluorocarbon copolymer, improving the overall high-temperature resistance and low-damage performance of the foam stabilizer.

[0021] According to another aspect of this application, a method for preparing the above-mentioned temperature- and salt-resistant carbon dioxide flooding foam stabilizer is provided, comprising the following steps: Add sulfonated betaine-fluorocarbon copolymer and fatty alcohol polyoxyethylene ether sulfonate to water in sequence, stir at low speed until completely dissolved, add aminotrimethylene phosphonic acid and carboxymethyl modified xanthan gum, continue stirring to disperse evenly, then add modified nano ZnO, stir at high speed, and finally add quaternized hydroxypropyl starch, stir at low speed, and let stand to obtain a temperature and salt resistant foam stabilizer for carbon dioxide flooding.

[0022] Specifically, the above preparation method involves adding materials in a specific order: first dissolving the organic components, then dispersing the nano-components, and finally adding starch-based additives. This avoids interference and agglomeration between components, ensuring uniform mixing of all components and maximizing their synergistic effect. The preparation steps are simple, require no complex equipment, and enable mass production, ensuring uniform and stable performance of the foam stabilizer and meeting the needs of on-site applications.

[0023] Optionally, the low-speed stirring speed is 150~200 rpm and the stirring time is 15~30 min; the high-speed stirring speed is 800~1000 rpm and the stirring time is 30~40 min; the settling time is 30~40 min.

[0024] Specifically, this application specifies the process parameters in the preparation method: low-speed stirring at 150-200 rpm can fully dissolve and disperse the organic components evenly, avoiding excessive stirring that could damage the component structure; high-speed stirring at 800-1000 rpm can prevent the modified nano-ZnO from agglomerating; and standing for 30-40 minutes can allow the system to mature and improve stability. These parameters ensure that the components work together fully, avoiding performance defects caused by uneven mixing, making the foam stabilizer system uniform and highly stable. At the same time, it simplifies the preparation process, reduces the difficulty of on-site operation, and ensures consistent product performance during mass production.

[0025] The beneficial effects of this application include, but are not limited to: 1. According to the temperature- and salt-resistant foam stabilizer for carbon dioxide flooding of oil, this application achieves strong salt resistance and CO2 extraction resistance through the synergistic effect of sulfonate betaine-fluorocarbon copolymer and fatty alcohol polyoxyethylene ether sulfonate, while also inhibiting the emulsification risks caused by fluorocarbon components; the synergistic effect of polydopamine-coated modified nano-ZnO and quaternized hydroxypropyl starch not only leverages the high-temperature resistance and anti-degradation properties of nanoparticles and strengthens the foam film, but also solves the problems of adsorption damage and pore throat blockage; aminotrimethylene phosphonic acid and carboxymethyl modified xanthan gum provide auxiliary enhancement, comprehensively solving the pain points of existing foam stabilizers such as insufficient salt resistance, high-temperature failure, and nano-adsorption, and is suitable for the harsh environment of high-temperature and high-salt oil reservoirs.

[0026] 2. The temperature- and salt-resistant foam stabilizer for carbon dioxide flooding according to this application chelates high-valence metal ions through the sulfonate groups of sulfonate betaine-fluorocarbon copolymer, the sulfonate groups of fatty alcohol polyoxyethylene ether sulfonate, and aminotrimethylene phosphonic acid, thus preventing salting out and precipitation; the polydopamine coating can capture high-temperature free radicals and prevent thermal degradation of components; the synergistic effect of each component results in strong shear resistance and anti-bubble aggregation ability, significantly improving the foam half-life, achieving long-term formation foam stabilization, effectively inhibiting CO2 gas channeling, expanding the oil displacement sweep volume, and improving crude oil recovery.

[0027] 3. The preparation method of the temperature- and salt-resistant carbon dioxide flooding foam stabilizer according to this application is simple and controllable. The preparation steps of the core components are scientific and industrializable. On-site preparation does not require complex equipment, which is conducive to large-scale industrial promotion and utilization. Detailed Implementation

[0028] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of skill in the art. The reagents and raw materials used in this invention are readily available through conventional means, and unless otherwise specified, they shall be used in accordance with conventional methods in the art or as per the product instructions. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to the methods of this invention. The preferred embodiments and materials described in this patent are for illustrative purposes only.

[0030] Example 1: Preparation of a temperature- and salt-resistant foam stabilizer for carbon dioxide flooding: According to the following formula, 0.8% betaine sulfonate-fluorocarbon copolymer, 0.12% fatty alcohol polyoxyethylene ether sulfonate, 0.2% modified nano-ZnO, 0.08% quaternized hydroxypropyl starch, 0.05% aminotrimethylene phosphonic acid, 0.05% carboxymethyl modified xanthan gum, and the balance being water, the raw materials were taken, and the betaine sulfonate-fluorocarbon copolymer and fatty alcohol polyoxyethylene ether sulfonate were added to the water in sequence. The mixture was stirred at low speed until completely dissolved. The stirring speed was 150 rpm and the stirring time was 15 min. Then, aminotrimethylene phosphonic acid and carboxymethyl modified xanthan gum were added and stirred until evenly dispersed. Then, modified nano-ZnO was added and stirred at high speed. The stirring speed was 800 rpm and the stirring time was 30 min. Finally, quaternized hydroxypropyl starch was added and stirred at low speed. The mixture was stirred at low speed. The stirring time was 150 rpm and the stirring time was 15 min. After standing for 30 min, a temperature- and salt-resistant foam stabilizer for carbon dioxide flooding was obtained.

[0031] Preparation of sulfonate betaine-fluorocarbon copolymer: S1. Methacryloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate, and hydroxyethyl methacrylate are placed in a three-necked flask with a molar ratio of 7:3:0.5. DMSO solvent is added, with the amount of DMSO solvent being 3 times the total mass of methacryloyloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate, and hydroxyethyl methacrylate. The mixture is heated to 70°C and stirred. S2 was added dropwise under a nitrogen atmosphere. The initiator solution was 5% azobisisobutyronitrile. The amount of initiator was 2% of the total mass of methacryloyloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate and hydroxyethyl methacrylate. The reaction was stirred at 70°C for 6 hours. S3 was cooled to 50°C, and an isocyanate propyltriethoxysilane solution with a mass concentration of 8% was added dropwise. The solvent for the isocyanate propyltriethoxysilane solution was anhydrous ethanol. The reaction was stirred for 2 hours, cooled to room temperature, precipitated with anhydrous ethanol, centrifuged, washed, and dried to obtain sulfonate betaine-fluorocarbon copolymer.

[0032] Preparation of modified nano-ZnO: S01. Nano ZnO was dispersed in Tris-HCl buffer solution with a mass-to-volume ratio of 5 g / L. The mixture was ultrasonically dispersed for 30 min to obtain a uniformly dispersed nano ZnO suspension. Dopamine hydrochloride was added to the SO2 nano-ZnO suspension, with the amount of dopamine hydrochloride being 40% of the mass of nano-ZnO. The mixture was stirred and self-polymerized for 12 hours at room temperature and in an air atmosphere, so that dopamine was deposited in situ on the surface of nano-ZnO to form a polydopamine coating layer. After the SO3 reaction was completed, the precipitate was collected by centrifugation, washed with deionized water, and dried at 50°C to obtain modified nano-ZnO.

[0033] Example 2: Preparation of a temperature- and salt-resistant foam stabilizer for carbon dioxide flooding: According to the following formula, 1.2% betaine-fluorocarbon copolymer, 0.2% fatty alcohol polyoxyethylene ether sulfonate, 0.3% modified nano-ZnO, 0.12% quaternized hydroxypropyl starch, 0.10% aminotrimethylene phosphonic acid, 0.08% carboxymethyl modified xanthan gum, and the balance being water, the raw materials were taken, and the betaine-fluorocarbon copolymer and fatty alcohol polyoxyethylene ether sulfonate were added to the water in sequence. The mixture was stirred at low speed until completely dissolved at 200 rpm for 30 min. Then, aminotrimethylene phosphonic acid and carboxymethyl modified xanthan gum were added and stirred until evenly dispersed. Then, modified nano-ZnO was added and stirred at high speed at 1000 rpm for 40 min. Finally, quaternized hydroxypropyl starch was added and stirred at low speed at 200 rpm for 30 min. After standing for 40 min, a temperature- and salt-resistant foam stabilizer for carbon dioxide flooding was obtained.

[0034] Preparation of sulfonate betaine-fluorocarbon copolymer: S1. Methacryloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate, and hydroxyethyl methacrylate are placed in a three-necked flask with a molar ratio of 8:2:0.6. DMSO solvent is added, with the amount of DMSO solvent being 4 times the total mass of methacryloyloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate, and hydroxyethyl methacrylate. The mixture is heated to 75°C and stirred. S2 was added dropwise under a nitrogen atmosphere. The initiator solution was 6% azobisisobutyronitrile. The amount of initiator was 3% of the total mass of methacryloyloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate and hydroxyethyl methacrylate. The reaction was stirred at 75°C for 8 hours. S3 was cooled to 55°C, and a propyltriethoxysilane isocyanate solution with a mass concentration of 10% was added dropwise. The solvent for the propyltriethoxysilane isocyanate solution was anhydrous ethanol. The mixture was stirred for 3 hours, cooled to room temperature, precipitated with anhydrous ethanol, centrifuged, washed, and dried to obtain the sulfonate betaine-fluorocarbon copolymer.

[0035] Preparation of modified nano-ZnO: S01. Nano ZnO was dispersed in Tris-HCl buffer solution with a mass-to-volume ratio of 8 g / L. The mixture was ultrasonically dispersed for 60 min to obtain a uniformly dispersed nano ZnO suspension. Dopamine hydrochloride was added to the SO2 nano-ZnO suspension, with the amount of dopamine hydrochloride being 60% of the mass of nano-ZnO. The mixture was stirred and self-polymerized for 16 hours at room temperature and in an air atmosphere, so that dopamine was deposited in situ on the surface of nano-ZnO to form a polydopamine coating layer. After the SO3 reaction was completed, the precipitate was collected by centrifugation, washed with deionized water, and dried at 60°C to obtain modified nano-ZnO.

[0036] Example 3: Preparation of a temperature- and salt-resistant foam stabilizer for carbon dioxide flooding: According to the following formula: 1% sulfonated betaine-fluorocarbon copolymer, 0.16% fatty alcohol polyoxyethylene ether sulfonate, 0.25% modified nano-ZnO, 0.1% quaternized hydroxypropyl starch, 0.08% aminotrimethylene phosphonic acid, 0.07% carboxymethyl modified xanthan gum, and the balance being water, take the raw materials, add sulfonated betaine-fluorocarbon copolymer and fatty alcohol polyoxyethylene ether sulfonate to water in sequence, stir at low speed until completely dissolved, the stirring speed is 180 rpm, and the stirring time is 20 min. Add aminotrimethylene phosphonic acid and carboxymethyl modified xanthan gum, continue stirring until evenly dispersed, then add modified nano-ZnO, stir at high speed, the stirring speed is 900 rpm, and the stirring time is 35 min. Finally, add quaternized hydroxypropyl starch, stir at low speed, the stirring speed is 180 rpm, and the stirring time is 18 min. Let stand for 35 min to obtain a temperature and salt resistant foam stabilizer for carbon dioxide flooding.

[0037] Preparation of sulfonate betaine-fluorocarbon copolymer: S1. Methacryloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate, and hydroxyethyl methacrylate were placed in a three-necked flask with a molar ratio of 7.5:2.5:0.55. DMSO solvent was added, with the amount of DMSO solvent being 3.5 times the total mass of methacryloyloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate, and hydroxyethyl methacrylate. The mixture was heated to 72°C and stirred. S2 was added dropwise under a nitrogen atmosphere with an initiator solution of 5% azobisisobutyronitrile. The amount of initiator was 2.5% of the total mass of methacryloyloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate and hydroxyethyl methacrylate. The reaction was stirred at 72°C for 7 hours. S3 was cooled to 55°C, and a propyltriethoxysilane isocyanate solution with a mass concentration of 9% was added dropwise. The solvent for the propyltriethoxysilane isocyanate solution was anhydrous ethanol. The mixture was stirred for 2.5 h, cooled to room temperature, precipitated with anhydrous ethanol, centrifuged, washed, and dried to obtain the sulfonate betaine-fluorocarbon copolymer.

[0038] Preparation of modified nano-ZnO: S01. Nano ZnO was dispersed in Tris-HCl buffer solution with a mass-to-volume ratio of 6 g / L. The dispersion was ultrasonicated for 40 min to obtain a uniformly dispersed nano ZnO suspension. Dopamine hydrochloride was added to the SO2 nano-ZnO suspension, with the amount of dopamine hydrochloride being 50% of the mass of nano-ZnO. The mixture was stirred and self-polymerized for 14 hours at room temperature and in an air atmosphere, so that dopamine was deposited in situ on the surface of nano-ZnO to form a polydopamine coating layer. After the SO3 reaction was completed, the precipitate was collected by centrifugation, washed with deionized water, and dried at 55°C to obtain modified nano-ZnO.

[0039] Example 4 The difference between Example 4 and Example 3 is that the molar ratio of methacryloyloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate and hydroxyethyl methacrylate is 1:1:0.5, while all other aspects are the same.

[0040] Comparative Example 1 The difference between Comparative Example 1 and Example 3 is that the sulfonate betaine-fluorocarbon copolymer was replaced with an equal amount of methacryloyloxyethyl-N,N-dimethylpropanesulfonate, while the rest were the same.

[0041] Comparative Example 2 The difference between Comparative Example 2 and Example 3 is that the modified nano-ZnO was replaced with unmodified nano-ZnO, while all other aspects are the same.

[0042] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that Comparative Example 3 does not include quaternized hydroxypropyl starch, but all other aspects are the same.

[0043] Comparative Example 4 The difference between Comparative Example 4 and Example 3 is that the sulfonate betaine-fluorocarbon copolymer is 1.16%, and it does not include fatty alcohol polyoxyethylene ether sulfonate, while the rest are the same.

[0044] Experiment 1: Foam Stability Test The foam stabilizer and foaming agent prepared in the above examples and comparative examples were mixed to form a foaming agent oil displacement system. The foaming agent was sodium α-olefin sulfonate (14C) with a content of 0.4 wt%, the foam stabilizer with a content of 0.2 wt%, and the balance was simulated brine (mineralization of 100,000 mg / L). The experimental conditions were set (temperature 85℃, pressure 12 MPa), CO2 gas was introduced until the pressure stabilized, the stirring speed was 300 rpm, and stirring was carried out for 5 min. After uniform foam was formed, the half-life of the foam was tested on a visual high-temperature and high-pressure foam evaluation instrument. The test results are shown in Table 1 below.

[0045] Table 1. Results of foam stability test

[0046] Table 1 shows that the foam half-life of Examples 1-3 is >420 min, with Example 3 being the best example. The half-life of Example 4 is reduced because the monomer molar ratio deviates from the optimal range. The half-life of each comparative example is <240 min, with Comparative Example 4 being the worst. Comparative Examples 1-4 show a significant decrease in foam stability due to the lack of key components.

[0047] Experiment Example 2: Temperature and Salt Resistance Test Temperature resistance: The foam stabilizers prepared in the above examples and comparative examples were placed in a constant temperature water bath, the temperature was set at 150℃, and the mixture was kept at the constant temperature for 24 hours. The state of the system was observed. After being taken out and cooled to room temperature, the foam half-life was tested according to the method of Experimental Example 1. The change rate of foam half-life before and after constant temperature was compared. The test results are shown in Table 2.

[0048] Salt tolerance: The foam stabilizers prepared in the above examples and comparative examples were respectively mixed with an equal volume of high-salinity simulated formation water (2.0 × 10⁻⁶) from Experimental Example 1. 5 Add the salt (mg / L), stir well, let stand at room temperature for 24 hours, and observe the state of the system. Then, test the foam half-life according to the method of Experiment Example 1, and compare the change rate of foam half-life before and after adding salt. The test results are shown in Table 2.

[0049] Table 2. Test results of temperature and salt resistance performance.

[0050] Table 2 shows that the temperature and salt resistance change rates of Examples 1-3 are relatively low, with Example 3 showing the lowest change rate. Example 4 exhibits a decrease in temperature and salt resistance, which is attributed to improper monomer ratios. Comparative Examples 4 and 1 performed the worst, likely due to the absence of key components, rendering the system unable to withstand high-temperature and high-salt environments.

[0051] Experimental Example 3 Core Adsorption Loss Rate Referring to GB / T 29172-2012 "Core Analysis Methods", simulated cores dried to constant weight and of uniform size were immersed in the foam stabilizers of each example and comparative example for 24 hours at 85℃ and normal pressure. After rinsing, drying and weighing, the adsorption loss rate was calculated. The adsorption loss rate (%) = (mass of core adsorbent / initial mass of reagent) × 100%. The results are shown in Table 3.

[0052] Table 3 Results of Core Adsorption Loss Rate Test

[0053] Table 3 shows that the adsorption loss rates of Examples 1-3 were all ≤40%, with Example 3 having the lowest rate. The adsorption loss rate of Example 4 increased, which was attributed to improper monomer ratio affecting component compatibility and increasing adsorption capacity. The adsorption loss rates of all comparative examples were ≥56%, with Comparative Example 3 showing the highest adsorption loss rate from the core sample. This was attributed to the absence of quaternized hydroxypropyl starch. Comparative Example 2 had a higher loss rate, attributed to the easy aggregation and adsorption of nanoparticles, leading to a higher loss rate.

[0054] The above description is merely an embodiment of this application, and the scope of protection of this application is not limited to these specific embodiments, but is determined by the claims of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the technical concept and principles of this application should be included within the scope of protection of this application.

Claims

1. A temperature- and salt-resistant foam stabilizer for carbon dioxide flooding, characterized in that, The composition, by mass fraction, includes 0.8% to 1.2% sulfonate betaine-fluorocarbon copolymer, 0.12% to 0.2% fatty alcohol polyoxyethylene ether sulfonate, 0.2% to 0.3% modified nano-ZnO, 0.08% to 0.12% quaternized hydroxypropyl starch, 0.05% to 0.10% aminotrimethylene phosphonic acid, 0.05% to 0.08% carboxymethyl modified xanthan gum, with the balance being water; the modified nano-ZnO is prepared by polydopamine-coated nano-ZnO. The sulfonate betaine-fluorocarbon copolymer was prepared by the following steps: S1. Methacryloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate and hydroxyethyl methacrylate are placed in a three-necked flask, DMSO solvent is added, the temperature is raised to 70-75℃, and the mixture is stirred. S2 was added dropwise with an initiator solution under a nitrogen atmosphere, and the reaction was stirred at 70-75°C for 6-8 hours. S3 was cooled to 50-55℃, and a solution of isocyanate propyltriethoxysilane was added dropwise. The mixture was stirred for 2-3 hours, cooled to room temperature, precipitated with anhydrous ethanol, centrifuged, washed, and dried to obtain the sulfonate betaine-fluorocarbon copolymer. The molar ratio of methacryloyloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate and hydroxyethyl methacrylate is (7 ~ 8):(2 ~ 3):(0.5 ~ 0.6).

2. The temperature- and salt-resistant foam stabilizer for carbon dioxide flooding according to claim 1, characterized in that, The initiator solution is azobisisobutyronitrile with a mass concentration of 5% to 6%; the amount of the initiator is 2% to 3% of the total mass of methacryloyloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate and hydroxyethyl methacrylate.

3. The temperature- and salt-resistant foam stabilizer for carbon dioxide flooding according to claim 1, characterized in that, The mass concentration of the isocyanate propyltriethoxysilane solution is 8% to 10%; the solvent of the isocyanate propyltriethoxysilane solution is anhydrous ethanol; the amount of DMSO solvent used is 3 to 4 times the total mass of methacryloyloxyethyl-N,N-dimethylpropanesulfonate, perfluorohexylethyl acrylate and hydroxyethyl methacrylate.

4. The temperature- and salt-resistant foam stabilizer for carbon dioxide flooding according to claim 1, characterized in that, The preparation method of the modified nano zinc oxide includes the following steps: S01. Nano ZnO was dispersed in Tris-HCl buffer and ultrasonically dispersed for 30-60 min to obtain a uniformly dispersed nano ZnO suspension. Dopamine hydrochloride was added to the SO2 nano-ZnO suspension and stirred at room temperature and in air atmosphere for 12 to 16 hours to allow dopamine to be deposited in situ on the surface of nano-ZnO to form a polydopamine coating layer. After the SO3 reaction is complete, the precipitate is collected by centrifugation, washed with deionized water, and dried at 50-60℃ to obtain modified nano-ZnO.

5. The temperature- and salt-resistant foam stabilizer for carbon dioxide flooding according to claim 4, characterized in that, The mass-to-volume ratio of the nano-ZnO to the Tris-HCl buffer is 5-8 g / L; the amount of dopamine hydrochloride used is 40%-60% of the mass of the nano-ZnO.

6. The preparation method of the temperature- and salt-resistant foam stabilizer for carbon dioxide flooding according to any one of claims 1 to 5, characterized in that, Includes the following steps: Add sulfonated betaine-fluorocarbon copolymer and fatty alcohol polyoxyethylene ether sulfonate to water in sequence, stir at low speed until completely dissolved, add aminotrimethylene phosphonic acid and carboxymethyl modified xanthan gum, continue stirring to disperse evenly, then add modified nano ZnO, stir at high speed, and finally add quaternized hydroxypropyl starch, stir at low speed, and let stand to obtain a temperature and salt resistant foam stabilizer for carbon dioxide flooding.

7. The preparation method of the temperature- and salt-resistant carbon dioxide flooding foam stabilizer according to claim 6, characterized in that, The low-speed stirring speed is 150-200 rpm, and the stirring time is 15-30 min; the high-speed stirring speed is 800-1000 rpm, and the stirring time is 30-40 min; the settling time is 30-40 min.

Citation Information

Patent Citations

  • Method for preparing fluorine-containing modified amphoteric water-soluble polymer

    CN101519473A

  • Humidity-sensitive intelligent betaine fluorinated antifouling paint and preparation method thereof

    CN102676015A